Mechanisms of governance: coordination strategies in portuguese local governments - Rodrigues, Miguel (2008)
Recent changes in Public Administration brought local government management to a new era. In recent years we witnessed a huge transformation in this reality. Early forms of organization, control and coordination of public goods have been replaced by other forms of organization such as contracting-out, private/public partnerships and public enterprises and agencies. Using a transactions cost framework, along with financial situation analysis, environmental complexity and political degree of stability we seek to find relevant factors that drive local government choices regarding the coordination mechanisms in the provision of public services.